Impact of mechanical stratigraphy on fracture growth and propagation - Su, Xiaocen; Gong, Lei; Fu, Xiaofei; Wang, Yougong; Gao, Shuai; Wang, Jie; Qin, Xinnan; Luo, Hairong; Bao, Tianlu (Frontiers in Earth Science, 2023)
Since mechanical stratigraphy plays an important role in controlling nucleation, propagation and development of fractures. Fracture development pattern and development mode were defined in this paper via detailed description. Fracture growth and evolution in bedded rocks were numerically simulated. Results show that fracture growth and propagation are controlled by mechanical layer. Fractures are divided into bed-confined ones and throughgoing ones based on their spatial configuration with mechanical layer. Fractures preferentially nucleate and expand in mechanical layer and terminate at mechanical contact. After that, new fractures are generated between two adjacent fractures. No new fractures are further developed when stress reaches certain value, indicating a saturation state. Finally, throughgoing fractures are developed. Under the same stress field, the bed-confined fracture density is positively correlated with Young's modulus of mechanical layer and is negatively correlated with its thickness. Bed-confined fractures can extend to another mechanical layer to develop throughgoing fractures only under significant stress field or at mechanical contact with small thickness or minor difference in mechanical properties. Exploring impact of mechanical stratigraphy on fracture development and propagation in bedded rocks is of great significance to investigate fracture distribution in hydrocarbon reservoirs.